Major sports events and the transmission of SARS-CoV-2: analysis of seven case-studies in Europe - Signorelli, Carlo; Odone, Anna; Riccò, Matteo; Bellini, Lorenzo; Croci, Roberto; Oradini-Alacreu, Aurea; Fiacchini, Daniel; Burioni, Roberto (Acta Biomedica Atenei Parmensis, 2020)
letter without abstract